Mediatization of Politics
XII, 246 p.
Keywords: The first book-long analysis of the 'mediatization of politics', this volume aims to understand the transformations of the relationship between media and politics in recent decades, and explores how growing media autonomy, journalistic framing, media populism and new media technologies affect democratic processes.